VMware vSphere 5.x Datacenter Design Cookbook : Over 70 Recipes to Design a Virtual Datacenter for Performance, Availability, Manageability, and Recoverability with VMware vSphere 5.x /: Over 70 Recipes to Design a Virtual Datacenter for Performance, Availability, Manageability, and Recoverability with VMware vSphere 5.x. (2014) - Unknown
No abstract available